PERANAN PENYULUH PERTANIAN DALAM MENDUKUNG KEBERLANJUTAN AGRIBISNIS PETANI MUDA DI KABUPATEN MAJALENGKA - Oeng Anwarudin; Sumardjo Sumardjo; Arif Satria; Anna Fatchiya (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2020)
Those who have the opportunity to foster young farmers in rural areas are agricultural extension workers. Therefore, agricultural extension workers are required to play a role in maintaining the sustainability of young farmers' agribusiness. The research aims to analyze descriptively the role of agricultural extension workers and the sustainability of young farmers 'agribusiness, and analyze the influence of the role of agricultural extension workers, characteristics, entrepreneurial capacity and external factors on the sustainability of young farmers' agribusiness. The study was conducted in Majalengka, West Java. The population is young farmers. The sample was selected as many as 137 people using cluster random sampling techniques. The research variables consisted of the characteristics of young farmers, external support, the role of agricultural extension workers, entrepreneurial capacity and agribusiness sustainability. Data analysis techniques using descriptive statistical analysis and multiple regression. The results of the study concluded that the level of the role of agricultural extension workers, external factors, entrepreneurial capacity and the potential for agribusiness sustainability of young farmers remained in the low category. The sustainability of young farmers' agribusiness is affected by access to information and communication technology (ICT), external factors, the role of agricultural extension workers and entrepreneurial capacity. Thus to maintain the sustainability of agribusiness young farmers can be done through increasing access to ICT, strengthening the role of agricultural extension workers, external factors and the entrepreneurial capacity of young farmers.